Monetary policy conundrum in developed economies: Is the region different? - Ana Mitreska; Ljupka Georgievska; Gani Ramadani (National Bank of the Republic of Macedonia, 2020)
Ten years after the global crisis, it is more than certain that the context for monetary policy making has not returned to the pre - crisis "normal". Central banks, in advanced economies in particular, have deployed unprecedented measures to ensure proper functioning of financial markets, and to provide impetus to the economy. Despite the recent global recovery, uncertainties remain elevated and possible vulnerabilities come to the fore. At the same time, certain macro-economic linkages on which conventional monetary policy making was based on have been challenged. To streamline the matter, we will tackle few important issues, which as monetary policy makers we have been faced with. First, though the monetary accommodation helped the recovery, easy financing conditions might have encouraged excessive risk-taking and building of debt vulnerabilities. Second, inflation rate has been low for long, despite the wage growth in many countries, giving ground to the so called "wage - price puzzle", and questioning the traditional Phillips curve concept. Third, given the lingering monetary accommodation, policy space has narrowed, thus constraining the room for reaction if severe shocks occur. In this note, we will make an effort to transpose these challenges to the countries of the CESEE region and asses how relevant these global matters are for them.
Keywords: 330; Geldpolitik; Kreditrisiko; Lohn-Preis-Spirale; Osteuropa